Missed nursing care and Orlando's theory: an essential analysis - Ivo Cristiano Soares Paiva; Filipa Isabel Quaresma Santos Ventura; António Carlos Lopes Vilela; Isabel Maria Pinheiro Borges Moreira (Universidade Católica Portuguesa, Instituto de Ciências da Saúde, 2023)
Missed Nursing Care (MNC) is an emerging problem in care practice environments and nurses play a role as potential causal agents as they are responsible for the decision-making concerning nursing care along the nursing process. Given the increasing incidence of MNC and the harmful consequences it leads to in terms of care safety and quality, raising healthcare professionals' awareness of MNC is crucial if aiming to reduce its occurrence. The nursing philosophy underpinned on Orlando's Theory, sets the focus of the nursing practice in the relationship nursing-patient. It further establishes the discipline of the nursing process as a systematic way of evaluating and guaranteeing the satisfaction of the patients' needs. [In this article we argue that] such processes have the potential of being protective factors to the occurrence of MNC, and consequently promote the patient's safety and the quality of care.